Distributed Self-Government in Protocol Communities: An Introduction and Index of Examples. - BELL, TOM W. (Independent Review)
The article offers information on Distributed Self-Government in Protocol Communities. It mentions resulting Distributed- Governance Index organizes and summarizes the latest developments in the evolution of distributed-protocol communities and provides a framework for continuing observation of this rapidly developing field.